Factors associated with physiological postoperative pyrexia. Issue 1 (24th November 2019) - Fukuda, Taeko; Nishida, Masato
Abstract: Aim: Postoperative pyrexia is generally a physiological response to surgery. It is a common problem and burden for both patients and surgeons. This study aimed to investigate the incidence and duration of physiological postoperative pyrexia and to retrospectively identify the prognostic factors associated with it. Methods: We reviewed the medical records of 462 patients who underwent surgery for adenomyosis under general anesthesia. Postoperative pyrexia was defined as an axillary temperature of at least 38°C occurring for at least 4 h after the surgery up to the next morning. Long‐duration pyrexia was defined as a fever recovery period of >3 days. Results: Of the 367 patients included in this study, 234 (64%) developed postoperative pyrexia and 260 (71%) needed >3 days to recover the normal temperature (<37°C). Multivariate analyses revealed that the administration of an amino acid‐enriched solution and non‐administration of flurbiprofen were associated with postoperative pyrexia. Scale of surgery (bleeding volume + weight of removed adenomyosis and other tissue), body mass index, and decreased body temperature during surgery were not associated with postoperative pyrexia. Long‐duration pyrexia was associated with the scale of surgery but not with the administration of an amino acid‐enriched solution and flurbiprofen. Conclusion: More than half of the patients developed postoperative pyrexia. Postoperative pyrexia was related to the administration of an amino acid‐enriched solution and flurbiprofen. Long‐duration pyrexia was associated with the scale of surgery.